1993
DOI: 10.1038/bjc.1993.404
|View full text |Cite
|
Sign up to set email alerts
|

Tumourigenesis associated with the p53 tumour suppressor gene

Abstract: Summary The p53 gene is contained within 16-20 kb of cellular DNA located on the short arm of human chromosome 17 at position 17pl3.1. This gene encodes a 393-amino-acid nuclear phosphoprotein involved in the regulation of cell proliferation. Current evidence suggests that loss of normal p53 function is associated with cell transformation in vitro and development of neoplasms in vivo. More than 50% of human malignancies of epithelial, mesenchymal, haematopoietic, lymphoid, and central nervous system origin ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
1
6

Year Published

1994
1994
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 85 publications
(72 reference statements)
0
63
1
6
Order By: Relevance
“…Wild-type p53 prevents cells with damaged DNA from proliferation by arresting the cell division cycle until such damage is repaired or by pushing the damaged cell down an irreversible apoptotic pathway; however, mutant p53 is known to inhibit apoptosis (13,17,38). Immunohistochemical staining of p53 protein using a monoclonal antibody, (e.g., PAb 1801), which recognizes domains present in both the wild and mutated p53 proteins, was believed predominantly to detect mutated p53 protein because the wild-type p53 protein is rapidly degraded in routinely handled tissue (39).…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type p53 prevents cells with damaged DNA from proliferation by arresting the cell division cycle until such damage is repaired or by pushing the damaged cell down an irreversible apoptotic pathway; however, mutant p53 is known to inhibit apoptosis (13,17,38). Immunohistochemical staining of p53 protein using a monoclonal antibody, (e.g., PAb 1801), which recognizes domains present in both the wild and mutated p53 proteins, was believed predominantly to detect mutated p53 protein because the wild-type p53 protein is rapidly degraded in routinely handled tissue (39).…”
Section: Discussionmentioning
confidence: 99%
“…The following observations may help explain the data: (a) the p53 protein has a longer half-life in MEC than in human fibroblasts (3 h vs 30 min; Delmolino et al, 1993); (b) p53 is complexed by the SV40 T Ag and accumulates in infected cells (Bartek et al, 1993;Chang et al, 1993). The latter mechanism may account for the high levels of 'mutant' p53 found by immunological methods.…”
Section: Analysis Of P53 Mutationsmentioning
confidence: 95%
“…Although not all mutations lead to protein accumulation (Bennett et al, 1991;Lehman et al, 1991;Vahakangas et al, 1992), in many studies a correlation between the p53 protein detected immunocytochemically and p53 gene mutations has been found (Iggo et al, 1990;Midgely et al, 1992;Navone et al, 1993). However, recent research has shown that not all immunohistochemically detected p53 results from mutation in the p53 gene (Lane, 1992;Wynford-Thomas, 1992;Chang et al, 1993;Fisher et al, 1994). p53 overexpression has been observed in many malignancies, including 60-70% of lung cancers (Iggo et al, 1990;Soini et al, 1992).…”
mentioning
confidence: 99%
“…The wild-type p53 protein inhibits cell proliferation, and loss of this activity leads to neoplastic transformation (Finlay, 1993;Levine, 1993). This protein has a short cellular half-life and is usually present in normal cells, under normal physiological conditions, in extremely small amounts, making it undetectable by standard immunohistochemical techniques (Iggo et al, 1990;Rodrigues et al, 1990;Chang et al, 1993). Many mutations of the p53 gene, principally in exons 5-8 (Hollstein et al, 1991), lead to a functional inactivation of the -gene and a protein product unable to regulate transcription, ultimately resulting in deregulation of cell growth (Chang et al, 1993;Finlay, 1993;Minna, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation